The KEMAMPUAN EKSTRAK KULIT KAYU DUA SPECIES Macaranga DALAM MENGHAMBAT PERTUMBUHAN BAKTERI Enterococcus faecalis - Hidayat, Beri; Yusro, Fathul; Mariani, Yeni (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2019)
Infection in oral cavity, especially in teeth root canals are often faced by Indonesian people, and one of the causes is bacterium Enterococcus faecalis. Potential plants as an anti-bacterial are two species of Macaranga, namely Merkubung (Macaranga gigantea) and Mangpurang (M. triloba). This study aims to analyze the presents of secondary metabolites content of those two bark extracts, and their ability to inhibit the growth of E. faecalis. The research methods carried out were powder prepared, moisture content measurement, extracts yield determination, phytochemical assays, and anti-bacterial assay. The yield of ethanol extracts of M. gigantea bark was 9.18% (moisture content 9.15%), and M. triloba was 9.70% (moisture content 8.56%). These two extracts positively contain phenolic, tannin, saponin, terpenoids, flavonoids, and alkaloids. The concentration level of 100 mg/mL is the best concentration of two extracts to inhibit the growth of E. faecalis, and the M. gigantea is the best extract in inhibit the growth of E. faecalis.